Prototheca from bovine milk and associated minimal algaecide concentration of chlorhexidine and povidone-iodine in Taiwan - Hsieh, Jui-Chun; Hsieh, Yi-Feng; Chuang, Shih-Te (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2020)
Objective Protothecal mastitis has emerged and affected the dairy industries globally in last decades; however, little is known about the occurrence of Prototheca in Taiwan. The present study identified the Prototheca isolated from bovine milk and revealed the algaecide efficacy of 2 disinfectants.Material and methods From 2011 to 2014, a total of 176 Prototheca isolates were obtained from 10 625 milk samples collected from dairy cows in 24 Taiwanese dairy farms. Of these, 149 isolates were identified by biochemical tests and genotype differentiation with a specific PCR protocol. Minimal algaecide concentration (MAC) of chlorhexidine and povidone-iodine were obtained from 16 isolates by microdilution method.Results Almost all (n = 147) isolates were P. zopfii, and remaining 2 isolates were P. wickerhamii and unidentified, respectively. Based on molecular genotyping, all P. zopfii isolates belonged to genotype 2. The MAC of 2 commonly used disinfectants, chlorhexidine and povidone-iodine, against 16 P. zopfii isolates was 1.56–3.13 and 48.83–390.63 µg/ml, respectively.Conclusion This report revealed for the first time the prevalence and the predominant P. zopfii genotype 2 of bovine protothecal infection in Taiwan. In vitro algaecide efficacy indicated that both tested disinfectants were effective against P. zopfii.
Keywords: Udder infection; algae; disinfection